Penerapan Pendekatan Kooperatif Tipe Two Stay Two Stray Untuk Meningkatkan Partisipasi Belajar Mahasiswa Pada Mata Kuliah Pembelajaran Terpadu - Natriani Syam; Nurjannah Nurjannah; St. Maryam, M. (Prodi PGSD FIP UNM, 2017)
The use of conventional learning methods make communication in the learning process exists only in one direction so that students in general passive learning in the classroom and only a few are active to ask, answer and respond to learning. Though learning participation is one of the important factors in learning activities. It is reminded that the teaching and learning activities are held in order to provide learning experiences on the learner. If the students actively participate in learning activities likely learners will be able to extract meaning from that learning. One way that could make students participate in learning that is by applying the learning model. For the purpose of this study was to determine students' increased participation in integrated learning in the classroom C.83 UPP PGSD Parepare FIP UNM by using model two stay two stray. This type of research is classroom action research (PTK). Forms implementation consist of planning, action, observation and reflection. Lasts for two cycles of study. Data analysis technique used is descriptive qualitative data analysis techniques. Be concluded that the application of learning models two stay two stray on the subjects of integrated learning can improve students' participation in class C.83 UPP PGSD Parepare FIP UNM.Keywords: classroom action research, learning model Two Stay Two Stray, study participation